SOME PECULIARITIES OF LEXICO-GRAMMATICAL HOMONYMY (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article studies characteristic features of homonymy in contemporary English and Uzbek. It clarifies some peculiarities of lexico-grammatical homonymy in two languages.